UMP undergrads thrilled over RM200 aid, free internet - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2020)
KUANTAN: Universiti Malaysia Pahang (UMP) undergraduates described the one-off payment of RM200, part of the Prihatin Rakyat Economic Stimulus Package (Prihatin), as a most timely handout.